Crescimento e desenvolvimento de Panicum maximum cv. milênio IPR 86 adubado com nitrogênio em três alturas de planta - Souza, Fernando Henrique de (2010)
In the tropics, livestock production is virtually dependent on pasture. In Brazil, the exploitation of pastures extraction is done by providing in this way, the progressive degradation of pastures. As a result there is a continuing search for new and even miraculous grasses to replace those that were used, without bothering to correct the problems that led to a drop in pasture productivity. Probably, the problems of reduced productivity are linked to soil fertility and pasture management. The use of nitrogen fertilizers, in animal production systems in grazing, aims to increase the sustainability of the business, by increasing the longevity of the pasture. In systems with low management level / input, the replacement of nitrogen (N) primarily aims to ensure the sustainability of plant communities. Already in production systems and improved management uprighted, N, besides working on the sustainability of grazing, becomes the main nutrient controlling the plant and animal productivity, as the increased availability of N in the medium interferes positively on the factors morphology of grasses, stimulating its growth and, consequently, contributing to increased productivity of the pasture. The aim of this study was to evaluate the morphogenesis, production and nutritional Panicum maximum cv. Millennium IPR 86 fertilized with increasing doses of nitrogen at different cutting heights. The forages studied responded very well to nitrogen fertilization showing the best response at the highest dose applied, and the height of 90 cm was obtained the best yield response, which is the recommended height for the management of this forage. However if the goal is to provide a forage with a higher nutritional value it should be handled at the height of 80 cm.